Home Albumin Infusion Therapy, Another Alternative Treatment in Patients With Congenital Nephrotic Syndrome of the Finnish Type - Serramontmany, Eugènia; Muñoz, Marina; Fernández-Polo, Aurora; Morillo, María; Gómez-Ganda, Laura; Cañete-Ramírez, Carme; Ariceta, Gema (Frontiers in Pediatrics, 2021)
Background: Congenital nephrotic syndrome of the Finnish type (CNF) is a rare, severe glomerular disease caused by mutations in the NPHS1 gene, which codes for nephrin. It is characterised by massive proteinuria and severe edoema. Progression to end-stage kidney failure occurs during early childhood and the only curative treatment is kidney transplantation. Nowadays, patients need aggressive medical treatment, which includes daily albumin infusions (for months) until they get clinical stability to receive transplant. Objective: In our paediatric hospital, we implemented a multidisciplinary program for the home infusion of albumin with outpatient follow-up. The aim of the study was to assess the safety and efficacy of this program for the first four years of its implementation. Material and Methods: Retrospective observational study of CNF paediatric patients treated with home albumin infusion therapy from March 2014 to July 2018 at a tertiary care paediatric hospital. Information on albumin administration was obtained from the electronic prescription assistance program and details on clinical and care-related variables from the hospital's electronic information systems. Results: Four patients with CNF received albumin infusions for 18, 21, 22 months, and 3 years. The treatment was safe, and the complication rates were to be expected considering the severity of disease. Patients required a median of two hospital admissions a year (19 in total); 47% due to catheter-related complications, but there were just three catheter infections. Conclusions: In our experience, home albumin infusion therapy is safe and effective and helps to improve children health and quality of life.